How Does the Blue Economy Align with Sustainability? A Bibliometric Analysis of Trends and Themes - Apriantoro, Muhamad Subhi; Saifullah, Muhammad Fahmi; Hudaefi, Fahmi Ali (International Journal of Energy Economics and Policy, 2025)
Sustainability of the blue economy is attracting growing interest among academics as an economic strategy that leverages sustainable marine resources. This study aims to investigate the evolution of publication trends and map keywords that help identify the main themes in this field. A bibliometric analysis was conducted of 382 scientific articles indexed by Scopus from 2003 to 2024. Data were processed using R software, Microsoft Excel, and VOSviewer. The findings indicate an annual growth of 23.49% %in this area of study, with a publication peak in 2024. The United States ranks as the most productive country, whereas the University of British Columbia and Stanford University have emerged as the most researched institutions. Marine policies have been identified as the most relevant and documented resource. The analysis uncovered four primary themes in the study of blue economy sustainability: Environmental sustainability, sustainable oceans, water management and policy, and marine conservation. This study serves as a foundation for further exploration to enhance the understanding of the future sustainability of the blue economy.